Emotionally Intelligent Employees’ Work Outcomes: The Mediating Role of Organizational Commitment - Hasan Hüseyin Uzunbacak; Tuğba Erhan; Tahsin Akçakanat (Faculty of Economic and Business, 2022)
The present study examines the effect of emotional intelligence on turnover intention and organizational indifference, noting the mediating role of organizational commitment. The current model of the study is considered one of the first attempts in examining these variables in the tourism industry. The structural equation modeling has been used to analyze the sample consisting of hotel department managers who have direct contact with the customers. According to the research results, emotional intelligence and organizational commitment decrease turnover intention and organizational indifference of the hotel department managers. In addition, emotional intelligence has been positively associated with the employees' organizational commitment. Finally, it has been found that organizational commitment mediates the effect of emotional intelligence on turnover intention and organizational indifference. Managers at the hotels should have the high emotional intelligence to establish empathy and perseverance to avoid being indifferent. In order to do this, hotel managers’ commitment should be increased to perceive their job as their own.How to Cite:Uzunbacak, H. H., Erhan, T., & Ak akanat, T. (2022). Emotionally Intelligent Employees’ Work Outcomes: The Mediating Role of Organizational Commitment. Etikonomi, 21(1), 11-40. https://doi.org/10.15408/etk.v21i1.20541